2023
DOI: 10.3130/aija.88.212
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Distribution Structure of the Number of Hospital Beds and the Capacity of Long-Term Care Insurance Facilities From the Viewpoint of Regional Characteristics

Abstract: Using structural equation modeling for secondary medical areas throughout Japan in 2015Takuya KUSUNOKI, Tohru YOSHIKAWA, and Ryo SANUKI This research aims to clarify the related structure of the distribution of general, chronic phase, and psychiatric sickbeds and capacity of long-term care insurance facilities in secondary medical areas, The results are as follows:1. urbanity and depopulation, which are latent factors of regional characteristics, influence the latent factors of sickbed distribution, such as ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Moreover, "Universities with a faculty of medicine" tend to increase "Acute care abundance" and "Clinic care abundance (without beds)." A study by Kusunoki et al [25] reported that the number of universities with a faculty of medicine increases the adequacy of acute care medical resources. Although their study used data on the distribution of medical resources in 2015, our results support the validity of the model used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, "Universities with a faculty of medicine" tend to increase "Acute care abundance" and "Clinic care abundance (without beds)." A study by Kusunoki et al [25] reported that the number of universities with a faculty of medicine increases the adequacy of acute care medical resources. Although their study used data on the distribution of medical resources in 2015, our results support the validity of the model used.…”
Section: Discussionmentioning
confidence: 99%
“…"Universities with a faculty of medicine" in the urbanicity group tended to increase "Clinic care abundance (without beds)." This trend may be attributed to the tendency for universities with a faculty of medicine to be located in urban areas, as indicated by the study by Kusunoki et al [25].…”
Section: Analysis Based On Urbanicitymentioning
confidence: 95%
See 1 more Smart Citation
“…In total, there were 15 variables of the distribution of medical and care resources used in the second phase. These variables can be aggregated by SMA, with reference to the study by Kusunoki et al [ 23 ], and are presented in Table 5 [ 34 – 36 ]. The summary statistics are presented in Table 6 .…”
Section: Methodsmentioning
confidence: 99%
“…The findings revealed that medical care adequacy was deficient in urban and remote areas. The second study, conducted by Kusunoki et al [ 23 ], analyzed the interrelation between regional characteristics and medical and care resources using factor analysis and structural equation modeling (SEM) for SMAs nationwide in 2015. The results indicated that suburban areas with a higher concentration of older individuals tended to have better medical care adequacy, whereas urban areas tended to have higher acute care adequacy via universities with medical schools.…”
Section: Introductionmentioning
confidence: 99%